The Memorisers Of The Al Qur'an Among Visual Impairment Scholars. - Noornajihan Ja‘afar; Nur Atiqah Binti Abdul Aziz; Mahyuddin Hashim; Muhammad Hafiz Saleh (Zes Rokman, 2024)
International Journal for Studies on Children, Women, Elderly And Disabled, Vol. 4, (June) 2018 ISSN 0128-309X